2018
DOI: 10.1016/j.brainres.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Enteric nervous system manifestations of neurodegenerative disease

Abstract: Neurological disorders cause gastrointestinal (GI) symptoms that are debilitating and markedly diminish quality of life in patients. The enteric nervous system (ENS), the intrinsic nervous system of the GI tract that is often referred to as "the second brain", shares many features with the central nervous system. The ENS plays an essential role in regulating many GI functions including motility and fluid secretion. Enteric neuronal degeneration could therefore be responsible for the GI symptoms commonly observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 53 publications
1
85
0
3
Order By: Relevance
“…The APP transgenic mice develop accumulation of Aβ in the enteric neurons leading to a decrease in enteric neuron abundance, dysmotility, and increased vulnerability to inflammation. 20 Preliminary data confirm that changes in the ENS in APP overexpressing transgenic mice correlate with the disease expression. 22…”
Section: Enteric Nervous Systemmentioning
confidence: 63%
See 1 more Smart Citation
“…The APP transgenic mice develop accumulation of Aβ in the enteric neurons leading to a decrease in enteric neuron abundance, dysmotility, and increased vulnerability to inflammation. 20 Preliminary data confirm that changes in the ENS in APP overexpressing transgenic mice correlate with the disease expression. 22…”
Section: Enteric Nervous Systemmentioning
confidence: 63%
“…This connection also allows for the disease spreading. 20 In Parkinson's disease (PD) gastrointestinal dysfunction is present in almost 80% of the patients, preceding motor dysfunction. In fact, α-synucleinopathy of the ENS has been suggested to be an early indicator of PD pathology.…”
Section: Enteric Nervous Systemmentioning
confidence: 99%
“…2a). These results may explain why PD patients have dysfunctional ganglia neurons 25 . The observed lower network efficiency and accordingly increased ASPL in MINs might have important implications, i.e., energy and information within enteric ganglia neurons are possibly produced, shared and distributed less competently in the ganglia neurons of PD patients relative to healthy controls.…”
Section: Resultsmentioning
confidence: 88%
“…The gut microbiome's role in AD pathogenesis likely stems from the gut–brain axis, a bi‐directional communication pathway between the enteric and central nervous systems. Dysbiosis seen in the gut can also lead to increased expression of amyloid precursor protein in mice, which can increase an individual's risk for neuroinflammation (Chalazonitis & Rao, ). One prior study found that patients with AD had a higher abundance of gut Bacteroidetes and decreased abundance of Actinobacteria (Vogt et al, ).…”
Section: The Oral Cavity As a Rich Source For Potential Dementia‐relamentioning
confidence: 99%